PENGARUH PERAN GENDER DAN PEMELIHARAAN LINGKUNGAN MIKRO TERHADAP KESEJAHTERAAN SUBJEKTIF KELUARGA PETANI DATARAN TINGGI - Rahma, Atika; Puspitawati, Herien; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2015)
The study aimed to analyze the effect of gender roles and micro environment maintenance on subjective well-being of farmer families in Sindangjaya Village, Cipanas Sub-District, Cianjur District, West Java Province. Samples as much as 100 farmer families were selected purposively. Data was collected by interview and observation the home environment. The data collected include family characteristics, characteristics of the home environment, family problems (economic, home environment, and agriculture), micro environment maintenance (hygiene and health, pesticide management, children protection, and homeyard management), the division of gender roles (public, domestic, and social community), and family well-being (physical, economic, social, psychological, homeyard conditions, and garden conditions). Multiple linear regression analysis showed that family income (β=0,222, p<0,05), family problems (β=-0,294, p<0,01), and micro environment maintenance (β=0,250, p<0,01) significantly affects the subjective family well-being. Increasing the family income and better of micro environment maintenance can increase the family subjective well-being. Increasing the family problem will reduce the family subjective well-being. Meanwhile, gender roles no significantly effect on subjective family wellbeing.